Endometrioid Adenocarcinoma with High-Grade Transformation with Serous and Choriocarcinomatous Differentiation - A Case Report - Wakahashi, Senn (Ivyspring International Publisher, 2011)
A choriocarcinoma component with a malignant tumor is relatively rare. We present a case of an 85-year-old woman with mixed carcinoma, which was endometrioid adenocarcinoma with squamous differentiation, choriocarcinoma and a disseminated peritoneal nodule, which was papillary serous adenocarcinoma. The patient received surgery and conservative treatment. Twenty weeks after surgery, a recurring tumor appeared at the Douglas pouch. Histology showed that the recurring tumor was poorly differentiated carcinoma that was very different from the primary tumor. This case represents an unusual uterine corpus cancer with high-grade transformation with serous and choriocarcinomatous differentiation. This case also demonstrates the capacity of tumor cells to differentiate into divergent elements.